ADAPTASI NELAYAN BAJAU TERHADAP DAMPAK PERUBAHAN IKLIM DI PESISIR SOROPIA KABUPATEN KONAWE, SULAWESI TENGGARA - Satria Dewiyanti; Amar Ma'ruf; Lies Indriyani (Jurnal Ecogreen, 2019)
This study aims to identify the adaptation form of Bajau Fishermen to the impacts of climate change that they have felt or experienced in the coast of Soropia,  Konawe district. The data of this study were collected through observation and in-depth interviews to the respondents who were selected from several Bajau villages in the coast of Soropia by using purposive and snowball sampling methods. Additional information was obtained through literature study and secondary data sources from village officials and related institutions. The key respondents interviewed in this study were 24 fishermen who have experience in fishing operation over 10 years. The results showed that the impact of global climate change felt or experienced by the Bajau fishermen were the increased risk of fishing, reduced fish production, increased fishing costs, the ineffectiveness of fishing gear they used and the difficulty in determining fishing grounds. The forms of adaptation carried out by Bajau fishermen in the Soropia Coast to the changes in environmental conditions due to the climate change impact are utilizing the potential of coastal resources, changing capture areas, varying the use of fishing gear, and diversifying of livelihoods. Key Words :Adaptation, Bajau Fishermen, Climate Change, Impact